The Implementation of Blended Learning in Islamic Elementary Schools during the Covid-19 Pandemic - Wahyu Wulandari; Corrienna Abdul Talib (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2022)
Education in Indonesia has undergone many significant changes due to the Covid-19 pandemic, including its learning system. Blended learning is a combination of offline and online learning models. The purpose of this study is to describe the implementation of the blended learning model during the COVID-19 pandemic at the islamic elementary school level. Blended learning can be implemented either online or face-to-face. This qualitative descriptive study conducted observation, interviews, and documentation to collect the data. The blended learning model during the COVID-19 pandemic was potentially capable of delivering more innovative learning. However, several problems experienced by teachers, students, and parents were also noticed. Teachers’ problems included limited media to deliver material in online learning. Meanwhile, the student's problem lay in their lack of learning independence. While parents’ role in guiding their children was pivotal, not all parents were capable of doing it. Students could improve their understanding by confirming directly with the teacher during the offline class, and parents were helped by a direct explanation from the teacher during the offline class.